The complete genome sequence of the yogurt isolate Streptococcus thermophilus ACA-DC 2 - Alexandraki, Voula (Stand Genomic Sci, 2017)
Streptococcus thermophilus ACA-DC 2 is a newly sequenced strain isolated from traditional Greek yogurt. Among the 14 fully sequenced strains of S. thermophilus currently deposited in the NCBI database, the ACA-DC 2 strain has the smallest chromosome, containing 1,731,838 bp. The annotation of its genome revealed the presence of 1,850 genes, including 1,556 protein-coding genes, 70 RNA genes and 224 potential pseudogenes. A large number of pseudogenes were identified. This was also accompanied by the absence of pathogenic features suggesting evolution of strain ACA-DC 2 through genome decay processes, most probably due to adaptation to the milk ecosystem. Analysis revealed the existence of one complete lactose-galactose operon, several proteolytic enzymes, one exopolysaccharide cluster, stress response genes and four putative antimicrobial peptides. Interestingly, one CRISPR-cas system and one orphan CRISPR, both carrying only one spacer, were predicted indicating low activity or inactivation of the cas proteins. Nevertheless, four putative restriction-modification systems were determined that may compensate any deficiencies of the CRISPR-cas system. Furthermore, whole genome phylogeny indicated three distinct clades within S. thermophilus. Comparative analysis among selected strains representative for each clade, including strain ACA-DC 2, revealed a high degree of conservation at the genomic scale, but also strain specific regions. Unique genes and genomic islands of strain ACA-DC 2 contained a number of genes potentially acquired through horizontal gene transfer events, that could be related to important technological properties for dairy starters. Our study suggests genomic traits in strain ACA-DC 2 compatible to the production of dairy fermented foods.